Genetic diversity analysis of Iranian Nigella sativa L. landraces using SCoT markers and evaluation of adjusted polymorphism information content. Issue 1 (14th August 2015) - Mirzaei, Khaled; Mirzaghaderi, Ghader
Abstract : The genetic diversity of 39 Iranian black cumin ( Nigella sativa L.) landraces was analysed using 14 polymorphic Start Codon Targeted (SCoT) markers. A total of 106 bands ranging from 3 (for SCoT70) to 13 (for SCoT23) were observed. Of them, 33 (31%) bands were polymorphic with a mean of 1.65 bands per primer. Polymorphism information content (PIC) per primer ranged from 0.035 (for SCoT12) to 0.133 (for SCoT70), with an average of 0.078. Besides PIC, Simpson's diversity ( D ) index was also calculated for each SCoT marker as an indication of discrimination power across population. The D index was used to adjust the PIC of the SCoT markers. As the adjusted PIC (PICD = PIC × D) was calculated based on both the PIC and the rate of band dispersion, this reflected the informativeness of a dominant marker more precisely than PIC. Genetic relationships were estimated using Jaccard's similarity coefficient-generated values between different pairs of genotypes that varied from 80 to 97% with an average of 88%. These coefficients were applied to construct a dendrogram using the UPGMA algorithm. A high genetic similarity was observed that might be due to the fact that N. sativa is a self-pollinated plant not originated from Iran and might have been imported from the Mediterranean regions.